BEHAVIOR OF NATURAL AND TREATED SOIL WITH MICROORGANISMS UPON VARIOUS WATER CONTENT DUE TO DYNAMIC LOAD - Albert Allowenda PS; Ria A. A. Soemitro; Trihanyndio R. Satrya (Journal of Civil Engineering, 2022)
Liquefaction is a phenomenon where the saturated sandy soil experiences highly excess pore water pressure and loss of effective stress between soil particles simultaneously due to an earthquake. It will have an impact on building damage or failure which laid on sandy soil. Study location was selected at the New International Airport in Kulonprogo, Yogyakarta which was built on loose sandy soil and coincidentally categorized as highly earthquake zone. Based on this, an experiment model was carried out to analyze the behavior of sandy soil when stabilized with Aspergillus fungus as the microorganisms. The loads derived from dynamic loads (earthquake loads) and it will also analyze the changes of soil parameters after the soil stabilization. In a previous study using a fungus with the type of Rhizopus oligosporus, it resulted in a significant increase in soil consistency under certain conditions of water content. From the experiment, it is known that the appropriate percentage of soil mixture consists of ordinary sand with a percentage of 62% plus silt and clay with a percentage of 38%. Aspergillus fungus isolates at a concentration of 10-2 showed good tissue growth and without the presence of foreign substances.